Hyper-resolution in X-ray emission spectroscopy: integrating extended-range high energy resolution fluorescence detection and multiple-crystal spectrometry with advanced binary data splicing - Ramesh Rijal; Jack Stephens; Daniel Sier; Nicholas T. T. Tran; Truong V. B. Nguyen; Jonathan W. Dean; Pierce Bowman; Minh Dao; Paul Di Pasquale; Tony Kirk; Chanh Q. Tran; Shusaku Hayama; et al. (Journal of Synchrotron Radiation, 2025)
This study of manganese (Mn, Z = 25) introduces a novel combination of extended-range high energy resolution fluorescence detection (XR-HERFD), multiple-crystal spectrometers and advanced binary data splicing techniques to address challenges in X-ray emission spectroscopy. XR-HERFD enhances spectral precision by utilizing high-resolution crystal analysers and optimized detector configurations. The systematic application of these methods using multiple Bragg crystal analysers at Diamond Light Source has led to substantial improvements in data quality. Simultaneously, advanced binary data splicing integrates multiple datasets to correct distortions and improve resolution, resulting in sharper spectral features. Our results show a significant increase in peak counts and a notable reduction in full width at half-maximum (FWHM), with peak amplitudes increasing by 83% and resolution improving by 46%. These developments provide greater detail for X-ray absorption or emission spectra, offering valuable insights into complex materials, and permitting advances and breakthroughs in atomic relativistic quantum mechanics, chemical sensitivity of atomic transitions and modelling of solid-state effects.